1980
DOI: 10.1002/art.1780230310
|View full text |Cite
|
Sign up to set email alerts
|

Joint motion in the absence of normal loading does not maintain normal articular cartilage

Abstract: Articular cartilage from the knees of 4 dogs whose ipsilateral paws had been transected 6 weeks earlier (knee,,,,,), and from their contralateral knees (knee,,), was examined. Knee,,,,, did not bear weight as a result of the surgical procedure but active motion of the joint, determined with an angular displacement monitor during walking, was comparable to that of knee,,.. In comparison to knee,, cartilage, knee,,,, samples showed decreases in thickness, Safranin-0 staining of the matrix, and uronic acid conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
108
2
6

Year Published

1985
1985
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(122 citation statements)
references
References 25 publications
(4 reference statements)
6
108
2
6
Order By: Relevance
“…In the contact areas, i.e., at the patellar surface of the femur and on the condylar summits of the femur, the loss of GAGs was not prominent. This suggests that contact forces, even within the cast, suffice to better maintain normal cartilage matrix (9). Further evidence of this is the finding that in the knees contralateral to the casted ones, the increase in weight-bearing caused an increase in the GAG content of the articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…In the contact areas, i.e., at the patellar surface of the femur and on the condylar summits of the femur, the loss of GAGs was not prominent. This suggests that contact forces, even within the cast, suffice to better maintain normal cartilage matrix (9). Further evidence of this is the finding that in the knees contralateral to the casted ones, the increase in weight-bearing caused an increase in the GAG content of the articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…This was apparent when the uronic acid values were related either to the water content or to the DNA content of the tissues, since these were essentially the same in unloaded cartilage as in loaded cartilage. The similarity of water content values in loaded and unloaded cartilage suggests that normal unloaded cartilage is different from atrophic (10,25) or osteoarthritic cartilage (26,27) in which the uronic acid content is decreaseld but the water content is increased. Presumably, the hyperhydration in damaged cartilage reflects an abnormality in the collagen network of the tissue that permits the hydrophilic proteoglycans to expand their molecular domains (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that mechanical loading of articular cartilage affects the metabolism of chondrocytes and its biochemical composition [1,32,37]. Both animal and human studies have shown that the GAG content is higher in cartilage that is habitually loaded [19,33] or has a higher level of activity [39], whereas immobilization results in a reversible decrease in cartilage PG content [18,30].…”
Section: Introductionmentioning
confidence: 99%